New Military Career: Cybersecurity Specialist January 2018. (Career Planning & Adult Development Journal)
An interview with Elka Torpey, an economist in the Office of Occupational Statistics and Employment Projections, BLS is presented. Topics discussed include ways of securing their information technology (IT) systems; issues relating to the cybersecurity; and the important for cybersecurity analysts.